Process Optimisation and Nutritional Analysis of Extruded Ready-to-Eat Multigrain Snack from Cereals Enriched with Flaxseeds - Anamika Singh; Abha Sharma (Annals of Agricultural Research, 2023)
The aim of the present study is to produce healthier and tastier multigrain puffs using extrusion technology. The composite flour was prepared using finger millet, pearl millet, sorghum, soya and rice, further enriched with flaxseeds and dried fenugreek leaves. The effect of temperature, moisture and screw speed on the characteristics of the dried extrudates (radial expansion ratio, Water absorbance index (WAI), Water solubility index (WSI) and bulk density (BD) was investigated using response surface methodology (RSM). Highest expansion of the puffs was observed at lowest moisture content (14%), highest barrel temperature (120 °C) and at a screw speed of 400 rpm while, all the three variables showed positive effect on Water absorption index (WAI). Temperature and moisture also have positive effect on WSI as well as on Bulk density. On the other hand, screw speed exerted negative effect on both WSI and BD. The optimized combinations of independent variables for the optimized responses (expansion ratio, 2.33; WSI, 24.19; WAI, 6.16 and BD, 0.337) were found to be a barrel temperature of 120 oC, feed moisture content of 19.13% and screw speed of 461.13 rpm. The proximate analysis of the multigrain snack revealed its high protein (22 %), high fiber (2.8 %), high phenolic (17g/mg GAE) content with lower fat (4.24 %) content compared to the control puffs which contained only 6 % protein, 0.35 % fiber, 10g/mg GAE phenolics while, 21 % fat. Thus, the multigrain snacks are much healthier than the commercially available market puffs. From the result of sensory evaluation, it was observed that the multigrain formulated puff with flaxseeds were more accepted overall as compared to traditional formulated puff. The reason of this acceptance may be due to better taste and crunchy flavour because of the presence of methi leaves and flaxseeds in it. The storage studies revealed that the puffs are shelf stable upto 30 days with no rancid flavour and no significant change in % FFA value. However, after 30 days, the % FFA value increased significantly.